2014
DOI: 10.1002/jgt.21844
|View full text |Cite
|
Sign up to set email alerts
|

Vertex Cuts

Abstract: Given a connected graph, in many cases it is possible to construct a structure tree that provides information about the ends of the graph or its connectivity. For example Stallings' theorem on the structure of groups with more than one end can be proved by analyzing the action of the group on a structure tree and Tutte used a structure tree to investigate finite 2-connected graphs, that are not 3-connected. Most of these structure tree theories have been based on edge cuts, which are components of the graph ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…Thus in both cases we obtained a contradiction to the maximality of P , which proves our claim (11).…”
Section: Graphs Without Monochromatic Cyclessupporting
confidence: 63%
“…Thus in both cases we obtained a contradiction to the maximality of P , which proves our claim (11).…”
Section: Graphs Without Monochromatic Cyclessupporting
confidence: 63%
“…Extending results of Tutte [9] and of Dunwoody and Krön [5], three of us and Maya Stein showed that every finite graph G admits, for every integer k, a tree-decomposition (T, V) of adhesion < k that distinguishes all its k-blocks [3]. These decompositions are canonical in that the map G → (T, V) commutes with graph isomorphisms.…”
Section: Introductionmentioning
confidence: 78%
“…Indeed, as (A, V ) ≤ (V, A), a consistent set of separations containing (V, A) must not contain the inverse of (A, V ), which is (V, A). 5 Note that consistent sets of separations can contain improper separations of the form (A, V ).…”
Section: Separation Systemsmentioning
confidence: 99%
“…These are connected graphs that have more than one infinite component after removing finitely many vertices. We were able to develop such a theory in [14]. In the course of our work on this, we realised that we could develop a theory of structure trees for finite graphs that generalised the theory of Tutte [33], who obtained a structure tree result for 2-connected finite graphs that are not 3-connected.…”
Section: Introductionmentioning
confidence: 99%